Pengembangan Buku Pembelajaran IPA Dasar Berbasis TPACK Untuk Meningkatkan Hasil Belajar Siswa Kelas III Sekolah Dasar Negeri 16 Banda Aceh - Sari, Siti Mayang; Zahraini, Zahraini; Filina, Nurul Zikri (Jurnal Pendidikan Humaniora, 2024)
This research aims to develop a TPACK-based Basic Science learning book as an effort to improve the learning outcomes of class III students at State Elementary School 16 Banda Aceh. This research is a type of research and development (R&D), using the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The research results prove that the TPACK-based Basic Science learning book is suitable for use with media expert validation results in the very good category (93%), material expert validation in the very good category (94%), language experts showing the very good category (90%). The TPACK-based Basic Science Book can improve the learning outcomes of class III students at State Elementary School 16 Banda Aceh as proven by the evaluation of the results of the student test questions which obtained a result of 86% with very good criteria with details of 33 students completing it.